Influence of gold diffusion-doped on phase formation, superconducting and microstructure properties of Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oysuperconductors - Özgür, Öztürk; Akdoğan, Mustafa; Terzioğlu, Cabir; Gencer, Ali (IOP Publishing, 2009)
We report on low-field magnetic properties of gold diffusion-doped Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oy superconducting bulk samples by performing ac susceptibility measurements. The undoped samples were prepared by the standard solid-state reaction method. Doping of Bi1.8Pb0.35Sr1.9Ca2.1Cu3Oy was carried out by means of Au-diffusion during sintering from an evaporated gold film on pellets. To investigate the effect of gold-diffusion and diffusion-annealing duration on transport, magnetic and microstructure properties of the superconducting samples we performed magnetoresistivity, scanning electron microscopy (SEM) and X-ray diffraction (XRD) measurements. The ac susceptibility as a function of temperature measurements were carried out at different values of the ac magnetic field amplitudes (Hac) in the range between 20A/m and 320 A/m for 211 Hz. The imaginary part of ac susceptibility measurements is used to calculate intergranular critical current density Jc(Tp) using the Bean Model. Jc(Tp) is seen to increase from 60 A cm-2 to 90 A cm-2 with increasing diffusion-annealing time from 10 h to 50 h. The peak temperature, Tp, in the imaginary part of the ac susceptibility is shifted to a lower temperature with decreasing diffusion-annealing duration as well as increasing ac magnetic fields. The force pinning density (αjj (0)) increased with increasing diffusion annealing time. The value of Tc in gold-diffused samples, in comparison with the undoped samples, increased from 100 ± 0.2 K to 104 ± 0.2 K. It was observed that the value of Tc-offset of the gold-doped samples enhanced with further increasing diffusion-annealing duration. XRD patterns and SEM micrographs are used to obtain information about Bi-2223 phase ratio, lattice parameters and grain size of the samples. Gold doping enhanced the formation high-Tc phase and increased the grain size. The possible reasons for the observed improvements in transport, microstructure and magnetic properties due to Au diffusion and diffusion-annealing time were discussed.
Keywords: Superconducting; Bi1.8Pb0.35Sr 1.9Ca2.1Cu3Oy; Scanning Electron Microscopy; Microstructure